Dental attendance among low-income women and their children following a brief motivational counseling intervention: A community randomized trial. (November 2015) - Riedy, Christine A.; Weinstein, Philip; Mancl, Lloyd; Garson, Gayle; Huebner, Colleen E.; Milgrom, Peter; Grembowski, David; Shepherd-Banigan, Megan; Smolen, Darlene; Sutherland, Marilynn
Abstract: This study tested a behavioral intervention to increase dental attendance among rural Oregonian low-income women and their children. It utilized a multi-site, single-blind, randomized trial design. Four hundred women were randomized into one of four conditions to receive prenatal or postpartum motivational interviewing/counseling (MI) or prenatal or postpartum health education (HE). Counselors also functioned as patient navigators. Primary outcomes were dental attendance during pregnancy for the mother and for the child by age 18 months. Attendance was obtained from the Oregon Division of Medical Assistance Programs and participant self-report. Statewide self-reported utilization data were obtained from the Oregon Pregnancy Risk Assessment Monitoring System (PRAMS). Maternal attendance was 92% in the prenatal MI group and 94% in the prenatal HE group ( RR = 0.98; 95% CI = 0.93–1.04). Children's attendance was 54% in postpartum MI group and 52% in the postpartum HE group ( RR = 1.03; 95% CI = 0.82–1.28). Compared to statewide PRAMS, attendance was higher during pregnancy for study mothers (45% statewide; 95% CI = 40–50%) and for their children by 24 months (36% statewide; 95% CI = 27–44%). MI did not lead to greater attendance when compared to HE alone and cost more to implement. High attendance may be attributable to the counselors' patient navigator function. Trial Registration: ClinicalTrials.gov IdentifierNCT01120041 . Highlights: Dental attendance was similar between the motivational interviewing counseling and health education groups. Baby Smiles participants' dental attendance was higher than other Oregon women. Counselors' patient navigator role may have impacted dental attendance. Higher costs were incurred for counseling compared to health education only.